PEMANFAATAN APLIKASI BERBASIS DARING SEBAGAI PENDAMPING E-LEARNING PADA PERKULIAHAN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI - Fadhilah, Nurul; Ilmiah, Wardatul; Mubarok, Muhammad Ramdan (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This study aims to describe applications that can coexist with e-learning owned by campuses so that PAI learning in online-based universities can be efficient. Changes in the concept of teaching and learning that initially meet teachers or students directly, turn into learning can be anywhere, with unlimited space and time. The concept of online learning is still continuing after covid 19, universities are still conducting online lectures for several courses that are considered easy to understand even though they are taught online, one of which is the PAI course. Higher education already has online learning media that is easy to access, namely e-learning on several campuses called SPADA. The features offered in e-learning are quite a lot, but the use of e-learning certainly has limitations and lacks innovation. From this phenomenon, a companion application is needed that can help vary learning so that it is more interesting. Companion applications that can be used include; Canva, Google, Padlet, Zoom, Quiziz, whatsaap etc. This research is qualitative research. This study concludes that additional applications are needed in addition to e-learning, the use of these applications is expected to increase its own impact on students in learning PAI, so that in lectures not only the transfer of knowledge is expected but the transfer of value is not eroded.